2019
DOI: 10.1108/idd-07-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of digital library database resources on the productivity of academic research

Abstract: Purpose Digital library database resources have a significant impact on stimulating the research culture in higher education. The use of digital databases makes it possible to understand intellectual growth, research productivity, planning and identification of user information needs. Evaluating the effectiveness of user database resource utilization and research, the purpose of this study is to assist management in developing an excellent academic policy. Design/methodology/approach This study establishes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 46 publications
3
38
0
3
Order By: Relevance
“…This is because there is only one library in each district, and that remote areas do not have effective transportation means and technical infrastructure to access information resources in libraries. In the current society, public and academic libraries offer community access to their information repositories through a VPN (Rafi et al, 2018). It is only a dream for developing countries, as they are characterized by low literacy levels, poor technical infrastructure and inadequate budgets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because there is only one library in each district, and that remote areas do not have effective transportation means and technical infrastructure to access information resources in libraries. In the current society, public and academic libraries offer community access to their information repositories through a VPN (Rafi et al, 2018). It is only a dream for developing countries, as they are characterized by low literacy levels, poor technical infrastructure and inadequate budgets.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that private influence has weakened the legitimacy of public libraries (Widdersheim and Koizumi, 2017). Although academic libraries are in a better position rather than public libraries because of being an autonomous body in the matter of earning and lavishly using for enriching libraries with collections and database resources (Rafi et al, 2018). Apart from that, they have expert administrators and a group of intellectuals for better reforms and policy guidelines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the increasing demand and the importance of database resources for education and research, it was also important to know how many databases were made available to the public. Previous research conducted by (Rafi et al, 2018) proved that the resources of the digital library database have a significant impact on promoting research productivity, making plans, improving digital literacy, and determining user information needs in the age of technology. Thus, given the growing importance of the database in education and research, the data was also collected on the library website about the subscribed database provided by HEC and also verified by service specialists.…”
Section: Methodsmentioning
confidence: 99%
“…A study revealed that university librarians in Pakistan do not have sufficient digital abilities [27], and their digital skills differ according to their university environment. At the same time, academic libraries have less digital skills to protect digital content [28]. Many librarians do not have enough knowledge to secure software, use encryption and decryption techniques to protect data, understand data security knowledge, and protect access by assigning passwords and digital control systems to libraries.…”
Section: Literature Reviewmentioning
confidence: 99%